The Role of interpersonal communication in the empowerment of female heads of household in Cianjur, Indonesia - Saleha Rodiah,; Susanne Dida,; Eni MaryanI,; Normah Mustaffa, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The potential of female heads of households is very important to be developed, but unfortunately they have not been able to fully participate because they still have limited power and a weak position in society. To empower them, an empowerment program for female heads of households is carried out. This research describes efforts conducted by members of the program to overcome hindrances faced in their position as female heads of household, particularly within their roles in both domestic and public spaces. This study uses a case study approach in which data were collected using in-depth interviews to eight informants including PEKKA members, officers, and corresponding household members. Participatory observations are conducted in three months, looking into PEKKA-related activities and the informants daily practices. The findings from this study reveal that through close and dialogic communication processes between the female heads of household and PEKKA officers, they can openly share their problems and receive support to solve their problems. Interpersonal communication helps the female heads of household in gaining trust and becoming role models for their families. This form of communication also enables wives to gain their husbands’ trust and render them equal partners. It is concluded that through the processes of interpersonal communication, female heads of household can position themselves as subjects that challenge the impeding patriarchal values. Interpersonal communication in the PEKKA program, both as practice and shared knowledge, is considered effective as a means to empower female heads of household.